Reaching high-risk young adolescents: a process evaluation of a school based injury prevention programme. (7th October 2012) - Dingli, K; Buckley, L; Chapman, R; Reveruzzi, B; Sheehan, M
Abstract : Background: Adolescent injury is a serious public health concern. Adolescents classified as high-risk are a population most vulnerable to harm from injury due to increased engagement in risk-taking behaviour. Aims/Objectives/Purpose: The aim of this research is to evaluate responsiveness of high-risk young Australian adolescents (13–14 years) to a curriculum based injury prevention programme. Methods: Fifteen schools implemented the Skills for Preventing Injury in Youth (SPIY) programme in April to June 2012. Focus groups were conducted with a random sample of teachers after the conclusion of SPIY in July 2012.Teachers classified the risk-level of students based on perceptions of student engagement in risk-taking behaviour (eg, alcohol, violence, transport risks) and reported on dose, adherence, quality of process and participant responsiveness. Results/Outcomes: The findings of teacher focus groups are presented regarding perceptions of the implementation of the curriculum based injury prevention programme and perceived responsiveness for high-risk young adolescents. Programme strengths and weaknesses are reported in the context of meeting the needs of high-risk young adolescents and the amount of material high-risk young adolescents received in line with the SPIY curriculum. Significance/Contribution to the Field: Teachers provide insight into responsiveness of high-risk young adolescents for a curriculum based injury prevention programme as well as the way it is implemented for high-risk young adolescents. Findings of this research have the potential to enhance implementation of school based interventions for high-risk young adolescents who are still participating in mainstream schooling and maximise programme effect and sustainability.